Active Volatile Constituents in Perilla frutescens Essential Oils and Improvement of Antimicrobial and Anti-Inflammatory Bioactivity by Fractionation. Issue 8 (16th November 2016) - Lin, Li-Yun; Peng, Chiung-Chi; Wang, Hui-Er; Liu, Yen-Wei; Shen, Kun-Hung; Chen, Kuan-Chou; Peng, Robert Y.
Abstract: Perilla frutescens (L.) Britt Labiatae (Pl), known as "Zi-So" and widely grown in China (red cultivar, Rpl) and Japan (green cultivar, Gpl), is frequently served on "Sa-Shi-Mi" dishes. Considering whether the perilla leaves substantially possess antimicrobial activity, we prepared the essential oils (EO: EOr and EOg), the pentane and ether [E: E(rp) and E(gp)] subfractions, the aqueous [Rpl(w) and Gpl(w)] and ethanolic extracts [pl(E), Rpl(E) and Gpl(E)] to compare their biological activities. Results indicated Gpl(E) and Rpl(E) contained huge amount (in mg/100 g) of polyphenoilcs (1472±1.0 vs. 1269.8±1.7), rutin (20.8±0.8 vs. 11.4±0.6), quercetin (29.8±0.9 vs. 13.6±0.6), and lutein (13.9±0.7 vs. 14.2±0.8). The total number of volatile constituents present in EOr and EOg were 27 in each but different phytochemicals. The top five major constituents (in %) in EOr were perilla aldehyde (54.35%), limonene (23.81%), trans -caryophyllene (7.2%), cis, trans -α-farnescene (7.02%), and linalool (2.40%); that in EOg were perilla aldehyde (65.26%), limonene (12.49%), cis, trans -α-farnescene (7.31%), trans - caryophyllene (5.91%), and linalool (2.75%); The top two constituents in E(rp) were perilla aldehyde (93.19%) and linalool (4.02%); that of E(gp) were perilla aldehyde (84.40%) and linalool (5.03%). EO and E showed moderate DPPH free radical scavenging-, ferrous ion chelating-, superoxide anion- and H2 O2 -scavenging capabilities. At 1.0 mg/mL the Es always revealed to be superior to EOs against E. coli, S. aureus, V. parahemolyticus, and T. mentagrophytes . Amazingly, E was stronger than perilla aldehyde against S. typhimurium, . The cytotoxicity test indicated Gpl(E) was more toxic than Rpl(E) and the pl(E)s were more toxic than pl(w)s. Conversely, the pl(w)s showed stronger TNF-α suppressing activity than pl(E)s. The pentane subfractions were entirely ineffective. Conclusively, the Perilla EOs contain huge amount of polyphenoilcs, the Es exhibit the rather good antimicrobial and cytotoxic effects, while the pl(w)s possess rather promising anti-inflammatory effect, underlying the promising antimicrobial and antiinflammtory effects of perilla leaves.